Reduced mutual coupling MIMO antenna. Issue 2 (3rd June 2019) - Thirupathi, Maturi; Krishna, B. Hari
In this paper, a reduced mutual coupling 1 × 2 inset feed rectangular patch antenna is presented. The antenna elements are separated by a distance of λ0 /4 exhibiting excellent isolation of −55 dB at 5 GHz band. To improve the isolation between closely placed antennas, a compact planar meander line based electronic Bandgap structure (EBG) behaves like a double negative (DNG) material is placed between them. The proposed EBG structure is implemented on the MIMO antenna with continuous as well as discontinuous ground plane. It is found that the EBG structure with discontinuous ground plane improves at least 6 dB isolation between antenna elements than continuous ground. The proposed antenna structures are fabricated showing good agreement between simulated and measured results.